What do editors of medical journals think about opportunities and barriers to advancement in the publication of plain language summaries? A qualitative analysis - Karen Gainey; Kirsten McCaffery; Danielle Muscat (PLoS ONE, 2026)
Background Plain language summaries (PLSs) are short summaries of research articles written for a diverse audience, using plain, easy-to-understand language. Although they have been adopted by many health and medical journals, we have a limited understanding of how they are viewed by journal editors. This remains an important gap because of the role journal editors play in the decision-making process for the publication, implementation, and dissemination of PLSs. To address this, the aims of this qualitative study were to: (a) gain a better understanding of the decision-making process that governs the publication of PLSs at the journal and publishing group levels; (b) explore attitudes and perspectives of journal editors towards PLSs; and (c) identify and explore barriers and facilitators to the implementation of PLSs by journals and journal publishers. Methods and findings We conducted semi-structured interviews with 20 participants who represented 23 journals and eight publishers/publishing groups. Using reflexive thematic analysis, we developed five themes: (1) When good intentions clash with practical realities; (2) Whose job is it anyway?; (3) A cautiously optimistic approach to support from artificial intelligence (AI); (4) Blind spots and broken loops; (5) A ‘One size fits all’ approach doesn’t work: the need for novelty. Discussions with participants highlighted the differing approaches taken by journals to prioritising PLSs, often governed by barriers such as resource allocation and the need for standardisation within publishing groups. While many participants showed initiative to overcome barriers, often in their own time, they noted challenges associated with a lack of PLS readership data and role clarity in the PLS production and dissemination pipeline. Opinions were mixed on the integration of AI and the integration of alternate formats for PLSs. Conclusions By embracing technology such as artificial intelligence, integrating innovative formats and exploring distribution channels including via consumer groups and social media, journal publishers can help elevate and expand the reach of PLSs.